Corrupting climate change institutions from the inside Systemic Collusion in the Peruvian Forest Governance - (:unkn) unknown (Elsevier BV, 2024)
This article aims to contribute to the literature on natural resource corruption by analyzing the subnational political economy behind the little enforcement of anticorruption policies. Building on the political ecology approach to corruption, this artic...
Keywords: Cambio climático; Gobernanza forestal